Evaluation of the In Vitro and In Vivo Antioxidant Potentials of Aframomum melegueta Methanolic Seed Extract. (15th May 2014) - Onoja, Samuel Okwudili; Omeh, Yusuf Ndukaku; Ezeja, Maxwell Ikechukwu; Chukwu, Martins Ndubuisi
Abstract : Aframomum melegueta Schum (Zingiberaceae) is a perennial herb widely cultivated for its valuable seeds in the tropical region of Africa. The present study evaluated the antioxidant effects of methanolic seed extract of A. melegueta . The antioxidant effects were evaluated using in vitro, 2, 2-diphenylpicrylhydrazine photometric assay and in vivo serum catalase, superoxide dismutase and thiobarbituric acid reactive substance assay method. The extract (25–400  μ g/mL concentration) produced concentration dependent increase in antioxidant activity in 2, 2-diphenylpicrylhydrazine photometric assay. The extract (400 mg/kg) showed a significant (P < 0.05 ) increase in serum catalase and superoxide dismutase activity when compared with the control group. The extract (400 mg/kg) showed a significant (P < 0.05 ) decrease in the serum level of thiobarbituric acid reactive substance when compared with the control group. These findings suggest that the seed of A. melegueta has potent antioxidant activity which may be responsible for some of its reported pharmacological activities and can be used as antioxidant supplement.